COOPERATION GAMES IN THE TEACHERS TRAINING: THE EXPERIENCE ON THE PROGRAM "A UNIÃO FAZ A VIDA" IN ALTO MÉDIO URUGUAI REGION - R/S (Fiep Bulletin - online, 2011)
This article assesses the results from a research that investigated the impact that the Co-operative games are producing in the knowledge and in the teachers' teaching practices in public schools belonging to the Alto Médio Uruguai region in RS. This research carried out in four towns that implemented the program until 2004. The assumptions that gave rise to the research problem are: a) we live in times of social agendas that have boosted the individual positions and undermined the school as a significant learning experiences area; b) "cooperative games" express an experience "cooperation pedagogy"; c) the teachers signify their teaching practices from their own experience; d) motivations and challenges arising from areas located outside the education formal system walls that can change knowledge that teachers always include in the process. The LDBEN, the guidelines entailed and the "Cooperative Games" principles were a reference to the analysis of practices and educational processes in this paper. The knowledge problem that structured the study was: what is the impact that the Cooperative Games, on the Program called "A União Faz a Vida", is producing on the knowledge and p teachers pedagogical practices working in the public schools in Alto Uruguai region in RS? This is a qualitative / descriptive research. The actors researched: two to three teachers from each school participating in the Program. Instruments: document analysis, questionnaire and interview. The analytical process revealed that the guidelines of the Program designed by Sicredi, produced new forms of relationship with the school community: it is mainly enhanced dynamic cooperatives in the pedagogical process, in all subjects in the schools studied.
Keywords: Cooperative games; Teacher formation